"Reddimus urbem": Civic Order and Public Politics at the End of Norman Sicily. Issue 2 (3rd May 2020) - Byrne, Philippa
ABSTRACT: This article addresses the relationship between political change and political culture at the end of Norman Sicily. It argues that one distinctive feature of that culture can be brought to light through an examination of the events of the 1190s, as processes of political restructuring gathered pace under the Staufen. The article begins from Peter of Eboli's Liber ad honorem Augusti. This text depicts a Norman political culture with considerable space for public assembly and interaction between populus and king. This was a model that allowed different religious and linguistic groups to be constituted in direct relationship to the king, without the formal mediation of institutional structures. Indications of a distinctively Norman Sicilian "public sphere" can be found in other texts of the period. Peter offered this to Henry VI, as a model the Staufen emperor could follow to demonstrate the legitimacy of his rule.